Efektivitas Implementasi Inovasi Identitas Kependudukan Digital (IKD) pada Layanan KTP-el di Dinas Kependudukan dan Pencatatan Sipil Kota Tasikmalaya - Rahma Fauziah; Ishak Kusnandar; Iis Miati (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2026)
Innovation through the Digital Population Identity (IKD) application is a form of digitization of population administration services that aims to improve the effectiveness, efficiency, quality of public services and become a solution to problems in the Electronic Identity Card (KTP-el) service. The low level of IKD activation in Tasikmalaya City shows that innovation has not been effective and needs to be studied more deeply. Previous research has not examined the factors that cause innovation to be ineffective especially the level of public trust in digital security. This study aims to analyze the effectiveness of IKD innovations at the Tasikmalaya City Population and Civil Registration Office. The research method uses descriptive qualitative with data collection techniques through observation, in depth interviews and documentation. The research informants were selected purposively consisting of service providers and the IKD user community. The research was analyzed using the characteristics of public sector innovation and showed that some dimensions were not optimal, especially in the aspects of relative advantage, trustworthiness and compatibility. The results of the study show that the effectiveness of IKD innovation is influenced by limited socialization, activation procedures that are not fully digital, low public trust in digital data security, limited authority and budget support at the regional level. These findings indicate that the effectiveness of public sector innovation is not only determined by the characteristics of innovation, but also by institutional factors and public trust in the implementation process. This study recommends optimizing socialization, increasing public trust and strengthening coordination between agencies as well as developing studies in more diverse contexts for future research.